2002
DOI: 10.1080/00140130110115336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of speech presentation level on cognitive task performance: implications for auditory display design

Abstract: Speech displays and verbal response technologies are increasingly being used in complex, high workload environments that require the simultaneous performance of visual and manual tasks. Examples of such environments include the flight decks of modern aircraft, advanced transport telematics systems providing invehicle route guidance and navigational information and mobile communication equipment in emergency and public safety vehicles. Previous research has established an optimum range for speech intelligibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Other studies have shown that deficits in working memory affect the ability of older individuals to understand timecompressed speech, 63 while other authors report that interhemispheric processing is disrupted as a result of the aging process 56 and that older adults are disadvantaged in dual-task conditions if hearing thresholds are increased even 10 dB. 64 The findings with regard to the interrelationship between visual performance and cognition are, in many ways, similar to the findings reported between hearing and cognition. Visual impairment has been shown by some 65,66 to be a risk factor for cognitive decline among the elderly.…”
Section: Cognitive Capacitysupporting
confidence: 73%
“…Other studies have shown that deficits in working memory affect the ability of older individuals to understand timecompressed speech, 63 while other authors report that interhemispheric processing is disrupted as a result of the aging process 56 and that older adults are disadvantaged in dual-task conditions if hearing thresholds are increased even 10 dB. 64 The findings with regard to the interrelationship between visual performance and cognition are, in many ways, similar to the findings reported between hearing and cognition. Visual impairment has been shown by some 65,66 to be a risk factor for cognitive decline among the elderly.…”
Section: Cognitive Capacitysupporting
confidence: 73%
“…This supports the idea that sensory degradation, not increased confusion between the streams, is responsible for the dramatic effect of noise on recall of M2. In related recent work, it has been suggested that reduced absolute signal level (in the absence of noise) can also disrupt echoic persistence and hence performance on a secondary task (Baldwin and Struckman-Johnson 2002; Baldwin 2007). …”
Section: Discussionmentioning
confidence: 99%
“…For example, sentence sets with high cloze values allow an accumulation of context that will facilitate the elicitation of robust N400. Utilization of language materials such as the present set can also assist in understanding the relative influence of sensory and cognitive processes, and the susceptibility of these processes to age-related changes (Baldwin, 2007;Baldwin & Struckman-Johnson, 2002). The expanded database of high cloze probability sentences presented here will allow the use of standardized materials to facilitate comparisons across investigations for many years to come.…”
Section: Supplemental Materialsmentioning
confidence: 99%